Captopril Enhances Cardiac Vagal but Not Sympathetic Neurotransmission in Pithed Rats - Yoshinobu Takata; Takanori Arai; Shigeto Suzuki; Junichi Kurihara; Takashi Uezono; Yoko Okubo; Hitoshi Kato (Elsevier, 2004)
The effect of captopril on neurally evoked bradycardia and tachycardia was investigated in pithed rats. Captopril enhanced the vagal nerve stimulation-evoked bradycardia. Angiotensin I reduced the vagal bradycardia, which was reversed by subsequent administration of captopril. Bradykinin did not affect the neurally evoked bradycardia. Captopril and angiotensin I affected neither the exogenous acetylcholine-evoked bradycardia nor the sympathetic nerve stimulation-evoked tachycardia. These results suggest that the interruption of angiotensin II formation by captopril causes less presynaptic inhibition of acetylcholine release via angiotensin II receptors without affecting cardiac sympathetic neurotransmission. Keywords:: captopril, autonomic neurotransmission, rat heart